Cations and dications of heavier group 14 elements in low oxidation states - Swamy, V. S. V. S. N.; Pal, Shiv; Khan, Shabana; Sen, Sakya S. (Dalton Transactions, 2015)
Cations and dications of heavier group 14 elements in their low oxidation state have received widespread attention in recent years. The journey started with the isolation of a series of cations of the composition [(C5Me5)E:](+) [E = Si-Pb], followed by the more recent isolation of a Ge(II) dication encapsulated within a cryptand, a carbodiphosphorane stabilized [GeCl](+) monocation with a two coordinate Ge atom, Si(II) cations and dications stabilized by N-heterocyclic carbenes (NHCs), which highlights the ongoing growth and interest in the chemistry of tetrel(II) cations. This is presumably because the central atom (E) in these compounds contains two or three unoccupied valence orbitals as well as holds a lone pair of electrons. Such an electronic description represents ambiphilicity, which is of great interest for catalysis. The successful synthesis of divalent group 14 cations requires new synthetic strategies based on the sterically demanding neutral or monoanionic ligands, utilization of counter anions, and solvents with low nucleophilicity in order to minimize the degree of interactions with the cations. An alternative approach for the realization of divalent cations of group 14 elements is their coordination to the transition metals. This synthetic approach was successfully applied for the isolation of a range of transition metal coordinated divalent cations of group 14 elements. Apart from arousing academic interest some of these cations have found application as activators in the Ziegler-Natta polymerization of alkenes.

Carbazole substituted amidinato silylene: synthesis, bonding, and coordination behavior with coinage metals - Ghosh, Moushakhi; Tothadi, Srinu; Khan, Shabana (Organometallics, 2021)
In this work, the synthesis and characterization of a new carbazole substituted amidinatosilylene (1) and its coinage metal complexes 3-8 are being reported. Before the complexation reactions, we prepared [PhC(N+Bu)(2)Si(Cbz)-> Co(CO)Cp] complex (2) to estimate the sigma-donating strength of the newly synthesized silylene 1. Further, several commonly available coinage metal salts were utilized for the complexation reactions with 1, which afforded complexes 3-8. The solid-state structures of 1-8 have been validated by single-crystal X-ray diffraction studies, NMR spectroscopy, and mass spectroscopy. DFT studies were also performed to understand the bonding scenario of 1 and 3-7. Of note, 1 consists of a HOMO on its carbazolide moiety, and the HOMO-1 features the silylene character. We also compared the HOMO-LUMO gap of 1 with other amidinato silylenes having different N-substitutions.

Ce[N(SiMe3)2]3(THF)3-catal yzed hydroboration of CO2, esters and epoxides with pinacolborane: selective synthesis of methanol in multigram scale - Hossain, Md Jabed; Shah, Brij Kumar; Dash, Soumya Ranjan; Vanka, Kumar; Khan, Shabana (Chemistry-A European Journal, 2025)
In this work, we have reduced CO2 with HBpin to afford borylated methanol product selectively in similar to 99 % yield using Ce[N(SiMe3)(2)](3)(THF)(3) as a catalyst. This led to multigram scale isolation of methanol obtained from CO2 reduction via the hydrolysis of borylated methanol, this establishes the potential of Ce[N(SiMe3)(2)](3)(THF)(3) as an efficient homogeneous catalyst for the bulk scale methanol synthesis. A practical application of this catalytic system was also shown by reducing CO2-containing motorbike exhaust efficiently and selectively. Further, C-O bond activation of esters and epoxides using HBpin and 1-2 mol % of Ce[N(SiMe3)(2)](3)(THF)(3) at 60 degrees C afforded the borylated alcohols in good to excellent yields, which can easily be hydrolysed to the eco-friendly corresponding alcohol. The stoichiometric experiments were performed to prove the formation of in-situ generated cerium hydride [Ce]-H as an active catalyst.
Keywords: Cerium; CO2 reduction; Epoxide; Ester; Hydroboration; Lanthanides